DIFFERENTIATION STRATEGY IN BANGSRING UNDERWATERBANYUWANGI ECOTOURISM - Jodi Hapro Kelana; Zahera Mega Utama; Franky (BETRIK, 2024)
This research aims to explore the strategies implemented by the management of Bangsring Underwater Banyuwangi Ecotourism through the differentiation strategy model, including content, context, and infrastructure. The approach used in this research is qualitative with a descriptive research type. This research shows that Bangsring Underwater management uses a differentiation model to increase tourist visits post-COVID-19. In the content dimension, Bangsring Underwater actively innovates on conservation-based destination products. Second, in the context dimension, the management implements integrated digital media marketing with the Government's digital platforms and regularly collaborates with various stakeholders. Third, in theinfrastructure dimension, the management provides comprehensive services during COVID-19, including reservations, tour package promotions, tours in collaboration with the district government, homestays, Personal Protective Equipment (PPE), Dive Centers, and additional facilities and equipment.